HUBUNGAN PENGGUNAAN APLIKASI ZOOM DENGAN MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH - Sandra Herliyani Nur Imani; Kasmin Kasmin (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
The problem that often occurs when online learning is that the teaching and learning process is not conducive, due to environmental factors that make students not focus, as well as in online meetings between educators, education staff or school principals. This research was conducted to determine the relationship between the use of the zoom application and the quality of education in Madrasah Tsanawiyah throughout the city of Bandung. This research is descriptive, using a quantitative approach to the type of correlation. The data collection technique was using a questionnaire questionnaire. Based on the results of the study, it is known that the use of the zoom application has a significant relationship with the quality of education in Madrasah Tsanawiyah throughout the city of Bandung, with a significance value of 0.000. The correlation coefficient obtained is 0.540 and is at a moderate level of strength. The contribution of the variable is 29.1%